Extent and Impact of Farm Mechanisation in Hilly State of Himachal Pradesh - Raina, Aditi; Thakur, Rajesh; Kumar, Sanjeev (Indian Journal of Extension Education, 2021)
Farm mechanization has been identified as one of the critical inputs for increasing the productivity of land by ensuring timeliness of agricultural operations, increased labour work output per unit time by reducing efforts, drudgery and improved quality of farm operations. The present study was conducted in Kangra district of Himachal Pradesh. Primary data were collected from 80 farmers. The net savings in case of land preparation operations through mechanization were estimated at Rs. 4454, 2330 and 658/ha, in case of wheat, maize and paddy respectively. Similarly, through the mechanization of sowing operation, the net gain was highest in wheat followed by maize and paddy i.e. Rs. 3910, 2347 and 2551/ha. Through the adoption of various farm mechanization practices on sample farms, they were able to save 56 to 67 man days of human labour and 23 to 35 bullock days/ha in major crops. The total added expenses on account of inputs and hiring charges were ranging between Rs 10652/ha in maize to 13665/ha in paddy. Per hectare net savings through mechanization was to the tune of Rs 8531, 15152 and 5685/ha in case of maize paddy and wheat, respectively.
Keywords: Extent; Farm costs; Farm mechanization; Farm returns